Fathers’ Involvement with their 24-month-old Children - Reginato Gabriel, Marília (2017)
This study investigated father involvement at 24 months of a child’s life. Twenty seven fathers, aged 19 to 40, were interviewed. The fathers’ answers were analyzed using content analysis, based on three dimensions: interaction, availability, and responsibility. The results indicated that the fathers interacted with the children according to the specific needs and capabilities of their 24-month-olds, at a stage when they become more autonomous. The fathers reported that they were involved in care activities, especially helping the children to deal with their own demands. At the same time, the fathers were involved by interacting, being available and showing concern for their children. Nevertheless, the fathers’ participation was noticed as lower when compared to that of the mothers, even when the father shared care and responsibility.